2022
DOI: 10.3389/fphar.2022.1027566
|View full text |Cite
|
Sign up to set email alerts
|

Berberine prevents lethal EV71 neurological infection in newborn mice

Abstract: Enterovirus 71 (EV71) is the major pathogen causing fatal neurological complications of hand, foot, and mouth disease (HFMD) in young children. Currently no effective antiviral therapy is available. In the present study, we found that natural compound Berberine (BBR) displayed potent inhibitory effects on EV71 replication in various neural cells (IC50 of 2.79–4.03 μM). In a newborn mouse model of lethal EV71 infection, Berberine at 2–5 mg/kg markedly reduced mortality and clinical scores. Consistently, the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The present study con rmed that JEV not only replicated in the brain but also targeted DA neurons in vivo, causing decreases in the numbers of DA neurons and TH levels, affecting the secretion of dopamine, and promoting the onset of dyskinesia, con rming that JEV infection of DA neurons caused cell death. Neuroin ammation triggered by sustained action is present in infectious diseases such as JEV, enterovirus 71 (EV71) and porcine hemagglutinating encephalomyelitis virus (PHEV) [46][47][48]. The present study showed that dopaminergic neurons induced in ammation and pathological changes after JEV infection, which is consistent with the general facts.…”
Section: Discussionsupporting
confidence: 90%
“…The present study con rmed that JEV not only replicated in the brain but also targeted DA neurons in vivo, causing decreases in the numbers of DA neurons and TH levels, affecting the secretion of dopamine, and promoting the onset of dyskinesia, con rming that JEV infection of DA neurons caused cell death. Neuroin ammation triggered by sustained action is present in infectious diseases such as JEV, enterovirus 71 (EV71) and porcine hemagglutinating encephalomyelitis virus (PHEV) [46][47][48]. The present study showed that dopaminergic neurons induced in ammation and pathological changes after JEV infection, which is consistent with the general facts.…”
Section: Discussionsupporting
confidence: 90%
“…2021 ) by restoring the body’s overall balance to counteract the harmful effects of viral infections ( Chen and Ye, 2022 ). Numerous traditional Chinese medicines have been proven to possess antiviral properties ( Guan et al, 2020 ; Kang et al, 2021 ; Lee et al, 2021 ; Cui et al, 2022 ) capable of directly acting on viruses and stimulating the immune system to induce interferon production, thereby indirectly inactivating viruses ( Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Berberine (200 mg/kg, i.g., for 2 weeks) prevents brain tissue against ischemia–reperfusion injury damage induced by middle cerebral artery occlusion through decreasing MDA and nitric oxide levels and increasing SOD activity (Chu et al, 2017). Berberine (2 and 5 mg/kg, i.p., for 1 week) prevents lethal neurological infection caused by Enterovirus 71 (EV71) by inhibiting virus replication by the regulation of the Keap‐Nrf2 axis and ROS generation in astrocytes of the brainstem in newborn mice (Cui et al, 2022). Berberine (5 and 50 mg/kg, i.p., for 1 week) significantly protected gastric mucosa that induced by ethanol in mice by increasing expression of eNOS mRNA and inhibiting expression of iNOS mRNA (Pan et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Berberine may have potential applications for the prevention and treatment of viral and bacterial infections. ROS generation in astrocytes of the brainstem in newborn mice (Cui et al, 2022). Berberine (5 and 50 mg/kg, i.p., for 1 week) significantly protected gastric mucosa that induced by ethanol in mice by increasing expression of eNOS mRNA and inhibiting expression of iNOS mRNA (Pan et al, 2005).…”
Section: In Vitro Studiesmentioning
confidence: 99%